THE FAMILY VALUES IN THE CONSTELLATION OF THE REBELS IN SHAKESPEARES HENRY IV ( part 1) - Adhyanggono GM (Soegijapranata Catholic University, 2004)
It is hard to say that all of Shakespeares plays exclude the issues of parents, children and politics of power. Those issues are to a certain degree intertwined. As a case in point, Henry IV (part one) embodies such a mingled concept. It is quite appealing to highlight the complexity of the familial relationships among the characters and their vested interests which enhance the plot of the play. Shakespeare, in this case, proves to be very intelligent in moulding the issues.